Analisis kontinyu fermentasi bertahap: pembentukan asetat, aseton, dan etanol oleh b. Racerans sebagai model - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
This investigation was a part of the direct bioconversion of cellulose to microbial products is often called a simultaneous saccharafication and fermentation. Bacillus macerans is capable of producing, under certain conditions, acetone and ethanol by fermenting a wide variety of carbohydrates. Litlle work has been done to investigate the system since first two decades of this century. The aim of this study was to assess the potential use of B. macerans for the production of solvent together with an investigation of tha factors controlling solventogenesis. Typical solvents were produced alter an initial acidogenic growth phase in which the acetic was formed with a concomitant drop in pH. as in batch and single continous culture, growth is related primarily with acid production. It is only at slow growth rates (slow dilution rate) or after a primary producing acidogenic growth phase that solvents are produced. To improve the fermentation, its probably that a temporal and spacial separation of the growth phase and solventogenic phase would succeed in increasing the productivity and the yield of both cells and solvents of the system. The result show that in the first vessel, the highest solvent production was achieved at a dilution rate, of 0.372/h and was 125.93 mM of etanol and 16.75 mM ofaceton were produced, while the overall productivity was 1.07 g/lâ¢g and 1.20 g/l/h for ethanol and acetone respectively. The result of the second vessel show that there is no acetate produced over the dilution rates investigated. However, the highest solvent production was achieced at dilution rate 0.043/h and was 354.28 mM and 91.80 mM for ethanol and acetone respectively, which taking into account the dilution rate gave volumetric productivities for the whole system (total volume 4.8 1), of 0.702 g/l/h for ethanol and 0.229 g/l/h for acetone.